On the survival of intergranular coesite in UHP eclogite. (6th December 2017) - Wang, L.; Wang, S.‐J.; Brown, M.; Zhang, J.‐F.; Feng, P.; Jin, Z.‐M.
Abstract: Coesite is typically found as inclusions in rock‐forming or accessory minerals in ultrahigh‐pressure (UHP) metamorphic rocks. Thus, the survival of intergranular coesite in UHP eclogite at Yangkou Bay (Sulu belt, eastern China) is surprising and implies locally "dry" conditions throughout exhumation. The dominant structures in the eclogites at Yangkou are a strong D2 foliation associated with tight‐to‐isoclinal F2 folds that are overprinted by close‐to‐tight F3 folds. The coesite‐bearing eclogites occur as rootless intrafolial isoclinal F1 fold noses wrapped by a composite S1 –S2 foliation in interlayered phengite‐bearing quartz‐rich schists. To evaluate controls on the survival of intergranular coesite, we determined the number density of intergranular coesite grains per cm 2 in thin section in two samples of coesite eclogite (phengite absent) and three samples of phengite‐bearing coesite eclogite (2–3 vol.% phengite), and measured the amount of water in garnet and omphacite in these samples, and also in two samples of phengite‐bearing quartz eclogite (6–7 vol.% phengite, coesite absent). As coesite decreases in the mode, the amount of primary structural water stored in the whole rock, based on the nominally anhydrous minerals (NAMs), increases from 107/197 ppm H2 O in the coesite eclogite to 157–253 ppm H2 O in the phengite‐bearing coesite eclogite to 391/444 ppm H2 O in the quartz eclogite. In addition, there is molecular water in the NAMs and modal water in phengite. If the primary concentrations reflect differences in water sequestered during the late prograde evolution, the amount of fluid stored in the NAMs at the metamorphic peak was higher outside of the F1 fold noses. During exhumation from UHP conditions, where NAMs became H2 O saturated, dehydroxylation would have generated a free fluid phase. Interstitial fluid in a garnet–clinopyroxene matrix at UHP conditions has dihedral angles >60°, so at equilibrium fluid will be trapped in isolated pores. However, outside the F1 fold noses strong D2 deformation likely promoted interconnection of fluid and migration along the developing S2 foliation, enabling conversion of some or all of the intergranular coesite into quartz. By contrast, the eclogite forming the F1 fold noses behaved as independent rigid bodies within the composite S1 –S2 foliation of the surrounding phengite‐bearing quartz‐rich schists. Primary structural water concentrations in the coesite eclogite are so low that H2 O saturation of the NAMs is unlikely to have occurred. This inherited drier environment in the F1 fold noses was maintained during exhumation by deformation partitioning and strain localization in the schists, and the fold noses remained immune to grain‐scale fluid infiltration from outside allowing coesite to survive. The amount of inherited primary structural water and the effects of strain partitioning are important variables in the survival of coesite during exhumation of deeply subducted continental crust. Evidence of UHP metamorphism may be preserved in similar isolated structural settings in other collisional orogens.